eBay photos that sell : - Gookin, Dan (SYBEX, 2005)
eBay Photos That Sell teaches home-spun entrepreneurs how to create professional-quality product photos using a standard digital camera and a few handy tricks and inexpensive techniques. With page after page of inspiring examples and expert insights, you'll figure out how to capture everything from hats to wineglasses to MP3 players. You'll understand what makes one photo better than another and discover how to create images that viewers connect with--ones that evoke the "I must have this" feeling. Ultimately, it will help you attract customers and make sales, without investing a lot of time or money.